PREDICTORS OF USE OF LONG ACTING ANTIPSYCHOTICS IN PATIENTS WITH SCHIZOPHRENIA - Albayrak, Y.; Beyazyuz, M.; Ozturk, N.; Kuloglu, M. (Cambridge Univ Press, 2013)
[Abstract Not Available]
21st European Congress of Psychiatry -- APR 06-09, 2013 -- Nice, FRANCE